The Effect of Serine Protease Inhibitors on Airway Inflammation in a Chronic Allergen-Induced Asthma Mouse Model. (7th August 2014) - Lin, Chih-Che; Lin, Li-Jen; Wang, Shulhn-Der; Chiang, Chung-Jen; Chao, Yun-Peng; Lin, Joseph; Kao, Shung-Te
Abstract : Serine protease inhibitors reportedly attenuated airway inflammation and had antioxidant in multiorgan. However, the effects of the serine protease inhibitors nafamostat mesilate (FUT), gabexate mesilate (FOY), and ulinastatin (UTI) on a long-term challenged mouse model of chronic asthma are unclear. BALB/c mice (6 mice/group) were intratracheally inoculated with five doses of Dermatophagoides pteronyssinus (Der p; 50  μ L, 1 mg/mL) at one-week intervals. Therapeutic doses of FUT (0.0625 mg/kg), FOY (20 mg/kg), or UTI (10, 000 U/kg) were, respectively, injected intraperitoneally into these mice. Control mice received sterile PBS. At 3 days after the last challenge, mice were sacrificed to assess airway hyperresponsiveness (AHR), remodeling, and inflammation; lung histological features; and cytokine expression profiles. Compared with untreated controls, mice treated with FUT, FOY, and UTI had decreased AHR and goblet cell hyperplasia, decreased eosinophil and neutrophil infiltration, decreased Der p-induced IL-4 levels in serum and IL-5, IL-6, IL-13, and IL-17 levels in bronchoalveolar lavage fluid, and inhibited nuclear factor (NF)- κ B activity in lung tissues. The serine protease inhibitors FUT, FOY, and UTI have potential therapeutic benefits for treating asthma by downregulating Th2 cytokines and Th17 cell function and inhibiting NF- κ B activation in lung tissue.